Corporate Social Advocacy Communication Style on #TBSFightForSisterhood on Instagram - Suranto, Hanif; Bangun, Cendera Rizky Anugrah; Tjokrodinata, Charlie; Feego, Enric; Estherina, Brenda (Jurnal Visi Komunikasi, 2024)
Over the past years, companies have taken a new kind of social stand and publicly spoken on issues unrelated to their core business activities. The topics about gender equality rights or sexual harassment have become one of the main focuses on the corporate agenda, and companies have started advocating those issues actively. This phenomenon is then called corporate activism. This study discusses The Body Shop Indonesia's (TBSI) communication style in voicing corporate activism or corporate social advocacy through #TBSFightForSisterhood on Instagram. TBSI is engaging in corporate activism by addressing and advocating for controversial socio-political issues. This qualitative analysis study explores the themes The Body Shop Indonesia covers in its CSA communication and how The Body Shop frames CSA communication on Instagram. The analysis method used is visual and textual content analysis on Instagram. This study identified four communication frames in The Body Shop’s posts: informative, mobilizing, participatory, and aspirational. In conclusion, the most used communication style is informational, followed by mobilization, participation, and aspiration.